The Impact of Samarra’s scholars on Calling for Allah Almighty and Reforming society: Sheikh Abdul Aziz Al-Badri as a Model (Islamic Sciences Journal, 2024)
Samarra has historically been a prominent city, known for producing numerous scholars, writers, and poets. This fact is widely acknowledged. Sheikh Abd al-Aziz bin Abd al-Latif al-Badri is a notable figure among the sheikhs and Mujahideen due to his ancestral connection to Imam Jaafar al-Sadiq. Born in 1929, he was raised in a scholarly environment in Baghdad. He was instructed in religion by a group of Baghdad scholars, such as Sheikh Amjad Al-Zahawi, Sheikh Muhammad Al-Qazlaji, Sheikh Abdul Qadir Al-Khatib, Muhammad Fuad Al-Alusi, and additional individuals. He was an enthusiastic Islamic preacher and orator who fearlessly advocated for trust in God. He faced multiple detentions for his outspokenness and actively opposed the communist movement in Iraq during the reign of Abd al-Karim. He even issued a fatwa denouncing communists as non-believers and called for their defeat. Consequently, communists were not tolerated during his tenure. The government ordered a one-year confinement at home for him. President Ahmed Hassan al-Bakr was imprisoned and subsequently killed in 1969 AD.
Keywords: Samarra, Al-Dawah, Abdul Aziz, Al-Badri, Society.